THE POSSIBLE CAUSES OF INDONESIAN EFL STUDENTS’ ANXIETY IN SPEAKING IMPROMPTU SPEECH - Galuh Dwi Ajeng (International Conference on Education and Language (ICEL), 2016)
Impromptu speech gives a different experience in doing public speaking for students. This speech involves students in speaking what they have written in short time. While doing impromptu speech, many students who do not have a good skill in speaking choose to give up while others stand to speechless on the stage. This study is aimed to explore what causes appear related to foreign language anxiety among the English Education Study Program students in speaking impromptu speech. The data were gathered from a qualitative research. The sample of this study was a group of Indonesian students who took Speaking 3 class at STKIP PGRI Bandar Lampung. Impromptu speech was taught in this class. The results show that there were four causes of foreign language students’ anxiety: discomfort, fear, shyness, and worry. From the result of the study, some suggestions could be proposed to help the students deal with foreign language anxiety of Indonesian EFL students in speaking impromptu speech.